2023
DOI: 10.31235/osf.io/gdbj3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In the name of health and illness: An inquiry into Covid-19 vaccination policy in postsecondary education in Canada (published https://researchandappliedmedicine.com/revistas/vol1/revista6/vacunacion-covid-ingles.pdf)

Abstract: Since the launch of the Covid-19 global vaccination campaign in December of 2020, vaccination in postsecondary institutions has been a contested issue. International evidence indicates that these institutions have achieved high vaccination rates and Canadian public health agencies exclude them entirely from the list of institutions at risk of outbreaks. On the other hand, influential observers, and postsecondary institutions themselves insist that not only achieving, but also maintaining, “up-to-date” vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…There exists, to be sure, ample research on the perceived problem of "suboptimal" vaccine uptake or of vaccine hesitancy among HCWs, in Canada and elsewhere. As has been noted, most of this research, implicitly or explicitly, overwhelmingly endorses full and continuing vaccination for HCWs, if necessary through mandates (Chaufan et al, 2024). And there is little doubt that the policy of mandated vaccination has succeeded in increasing vaccination rates among HCWs (Lee et al, 2022;Poyiadji et al, 2022;Ritter et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…There exists, to be sure, ample research on the perceived problem of "suboptimal" vaccine uptake or of vaccine hesitancy among HCWs, in Canada and elsewhere. As has been noted, most of this research, implicitly or explicitly, overwhelmingly endorses full and continuing vaccination for HCWs, if necessary through mandates (Chaufan et al, 2024). And there is little doubt that the policy of mandated vaccination has succeeded in increasing vaccination rates among HCWs (Lee et al, 2022;Poyiadji et al, 2022;Ritter et al, 2021).…”
Section: Discussionmentioning
confidence: 87%
“…to embrace COVID-19 vaccination, so-called "vaccine hesitancy", cannot be informed by legitimate evidence, and that "in times of crisis" long-standing bioethical principles can, and should, "temporarily" be set asidefor instance, the principle of informed consent, established upon the "Doctors' Trial" in Nuremberg over half a century ago and subsequently upheld by leading international bioethical documents 31,32 . In addition, our research on the vaccination experience of postsecondary students also revealed that the high compliance observed among them has largely been driven by the understandable desire to "move on with life", by the very human emotional need for peer and societal acceptance, and by a nontrivial amount of bending to coercion given the significant material, social, and emotional costs of noncompliance 28 . Troublingly, compliance itself also appears to have borne significant emotional, when not physical, costs 5,17 .…”
mentioning
confidence: 88%
“…The letter of invitation indicates: (a) how the individual was identified, (b) the nature of the organizations involved in the project (ICES and Kidney Care Outreach research team), (c) details about the outreach intervention, (d) how to find out more information and consent to participate, and (e) frequently asked questions. Brochures from the Kidney Foundation are also included in the envelope [12]. Digital copies of the letter and envelope are available as online S2 Appendix.…”
Section: Plos Onementioning
confidence: 99%